«MOODLE LMS» МАСОФАВИЙ ЎҚИТИШ ТИЗИМИДАН ТАЛАБАЛАР МУСТАҚИЛ ТАЪЛИМИНИ ТАШКИЛ ЭТИШ - Алеўов, Ў.; Байдуллаев, А.С.; Рахманова, А.А. (SCIENCE and SOCIETY, 2019)
The author of the article briefly describes the Moodle LMS distance learning system, they study the main features of this system and advantages.
Keywords: information; information systems; information and communication technologies; Moodle LMS; e-education systems; the Internet; pharmaceutics